Gmina Klembów jako przykład realizacji lokalnej polityki gospodarczej - Juras, Anna; Kacprzak, Marzena (Zeszyty Naukowe SGGW, Polityki Europejskie, Finanse i Marketing, 2012)
The paper presents results of research carried out under the grant titled. he conditions of life and work of women in rural areas. The study was conducted in the Mazowieckie Province. Klembów, a rural commune, is one of the entities where the study was carried out. The commune has been evolving and seeking to overcome barriers of local development. The commune focuses on the development of core activities and key tasks concerning improvement of road, social and technical infrastructure. Year by year proportion of people using the water supply, sewage and gas has been increasing. It can be concluded that in the future this part of the technical infrastructure will be the biggest investment of an infrastructure. Investments carried out by Klembów also contribute to attractiveness of the commune in terms of investment or tourism. Development of technical infrastructure improves the competitiveness of the commune and leads to improving the standard of life of its community.